ANALISIS EFEKTIVITAS PENGGUNAAN MODAL KERJA PADA PT. METRODATA ELECTRONICS TBK - Marcella Reobita Lyan; M. Astri Yulidar; Rudy Syafariansyah (University of Widya Gama Mahakam Samarinda, 2019)
Effectiveness Analysis of Use of Working Capital at PT. Metrodata Electronics Tbk, The purpose of this study was to determine the effectiveness of the use of working capital at PT. Metrodata Electronics Tbk for 2015 until 2017. This research is a descriptive study based on quantitative data at PT. Metrodata Electronics Tbk. The variables used in this research are cash turnover, accounts receivable turnover, inventory turnover and ROI. Based on the results of the analysis and discussion above, it can be seen the effectiveness of the use of working capital at PT. Metrodata Electronics Tbk has experienced an increase in the period of 2015 to 2017 and ROI in companies is above the industry average so that it can be stated the effectiveness of the use of working capital has been effective in funding the company's daily operations.